A survey of the dialect geography of six towns of Zambales (Botolan, Iba, Palauig, Masinloc, Candelaria, and Sta Cruz) - Escudero, Estela Bundang 1932- (s.n.], 1969)
The study surveyed the dialect geography of six Zambal-speaking towns in the province of Zambales namely Botolan, Iba, Palauig, Masinloc, Candelaria, and Sta. Cruz. It uncovered the variations in forms of words having similar meanings on the bases of geographical location of the towns and age level of the speakers.